Centrosema pubescens Benth. (Fabaceae) reproductive biology - Borges, Hélida Bruno Nogueira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The pollination ecology and breeding system of the shrubby species Centrosema pubescens Benth. Was studied in the on tropical forest of Acre. The anthesis is diurnal and the flowers were visited by bees (9 spp.) and wasps (5 spp.) basicaly. The guild of pollination is composed by bees of the genus Xylocopa, Bombus, Euglossa, Exarete, Mesoplia, Megachile and Trigona and by wasps of the of the families Polybinae and Scoliidae. One species of bee and of moth behave as nectar thieves. The species is self-compatible but ptoduce fruit via selfing and outcrossing. Pollen vectors are not required for fruit set because the flower shows secondary presentation of pollen’s grain.